2012
DOI: 10.1016/j.physbeh.2011.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Strain differences in sucrose- and fructose-conditioned flavor preferences in mice

Abstract: Genetic factors strongly influence the intake and preference for sugar and saccharin solutions in inbred mouse strains. The present study determined if genetic variance also influences the learned preferences for flavors added to sugar solutions. Conditioned flavor preferences (CFP) are produced in rodents by adding a flavor (CS+) to a sugar solution and a different flavor (CS−) to a saccharin solution (CS−) in one-bottle training trials; the CS+ is subsequently preferred to the CS− when both are presented in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
47
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 38 publications
(55 citation statements)
references
References 43 publications
5
47
3
Order By: Relevance
“…The present experiment is the first to report that rodents learn to prefer a sugar-paired flavor over a sucralose-paired flavor, but there are several reports of similar conditioning using saccharin as the nonnutritive sweetener (9,18,27,34,43,61). However, in these earlier studies, the sugar (sucrose, glucose, fructose) was initially preferred to the saccharin so that the conditioned preference could be due to the taste of the sugar, its post-oral actions, or both properties.…”
Section: Discussionmentioning
confidence: 59%
“…The present experiment is the first to report that rodents learn to prefer a sugar-paired flavor over a sucralose-paired flavor, but there are several reports of similar conditioning using saccharin as the nonnutritive sweetener (9,18,27,34,43,61). However, in these earlier studies, the sugar (sucrose, glucose, fructose) was initially preferred to the saccharin so that the conditioned preference could be due to the taste of the sugar, its post-oral actions, or both properties.…”
Section: Discussionmentioning
confidence: 59%
“…In a recent study, Pinhas et al (24) investigated preference conditioning by orally consumed flavored sucrose, fructose, and saccharin solutions in nine mouse strains. All strains learned to prefer the sucrose-paired flavor over the saccharinpaired flavor, although they varied in the magnitude of their preferences (FVB mice were not included in the study).…”
Section: Discussionmentioning
confidence: 99%
“…Conceivably, strain differences in post-oral sugar appetition may contribute to variations in sugar intake in mice, but this has yet to be documented. One study reported mouse strain differences in sugar-conditioned flavor preferences, but because the sugars were orally consumed, the conditioning effects may have been mediated by the taste and/or post-oral actions of the sugars (24). In another study, we compared IG sucrose conditioning in C57BL/6J (B6) and 129 mice, which have the Sac B and Sac D variants of T1r3 receptor and, thus, are sweet sensitive and subsensitive, respectively (35).…”
mentioning
confidence: 99%
“…Correspondingly, marked strain differences occurred in the reduction of fat (Intralipid) following NTX and SCH in 8 inbred strains (Dym et al, 2010). In addition to the intrinsic palatability of sugars, sucrose and fructose elicit conditioned flavor preferences (CFP) that are also subject to marked differences across 8 inbred strains (Pinhas et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Two of these inbred strains, SWR and BALB/c mice, displayed the most robust and durable sucrose-CFP (Pinhas et al, 2012) and thus Pharmacology, Biochemistry and Behavior 131 (2015) 13-18 were evaluated for DA D1 and opioid antagonist mediation of the expression and acquisition of sucrose-CFP (Dym et al, 2012). Whereas sucrose-CFP expression in both BALB/c and SWR mice was significantly reduced by SCH and NTX, sucrose-CFP acquisition was significantly reduced by NTX, but not SCH in BALB/c mice, and by SCH, but not NTX in SWR mice (Dym et al, 2012).…”
Section: Introductionmentioning
confidence: 99%